Hymenophyllum senterreanum Dubuisson & Deblauwe, sp. nov. (Hymenophyllaceae) and its relatives in western Central Africa - Dubuisson, Jean-Yves; Hennequin, Sabine; Droissart, Vincent; Deblauwe, Vincent (Phytotaxa, 2016)
The fern genus Hymenophyllum (Hymenophyllaceae) so far encompassed not more than five species in western Central Africa. New investigations into BRLU and P collections on Hymenophyllaceae specimens collected in western Central Africa allowed us to identify a new species for the area. The species Hymenophyllum senterreanum sp. nov. displays indusia with an original and particular campanulate-like shape, usually observed in the distinct trichomanoid lineage. It seems endemic to sub-montane rainforests of coastal west-south Cameroon and Equatorial Guinea, and is currently known only from four localities. The novelty is considered as Endangered according to IUCN Categories and Criteria. An updated key is proposed for the genus Hymenophyllum for the region.